Modulating oxytocin brain penetration via intranasal delivery and a novel conjugate peptide (OT-GET) - Wong, Sara Wei Ting (2022)
Oxytocin (OT), an endogenous hormone and neuropeptide has been highlighted for its therapeutic potential to modulate socio-behavioural deficits. However, OT’s high molecular weight and hydrophilicity limits the extent of central nervous system (CNS) brain penetration, highlighting a need to improve OT brain delivery. An alternative popular route of drug delivery is intranasal administration, which allows small peptides to bypass the blood brain barrier (BBB) and access the brain more directly. Yet, the degree of OT brain penetration remains controversial and requires further improvement. As such, this thesis examined the modulation of CNS OT penetration by use of intranasal OT alone and when conjugated to a novel cell penetrating peptide: glycosaminoglycan (GAG)-binding enhanced transduction (GET; P21-LK15- 8R), producing OT-GET, and its ability to affect locomotor activity and social behaviour in rats.